ACBD3 is required for FAPP2 transferring glucosylceramide through maintaining the Golgi integrity. (10th May 2018) - Liao, Jing; Guan, Yuxiang; Chen, Wei; Shi, Can; Yao, Dongdong; Wang, Fengsong; Lam, Sin Man; Shui, Guanghou; Cao, Xinwang
Abstract: Glycosphingolipid (GSL) metabolism is involved in various physiological processes, including all major cell signaling pathways, and its dysregulation is linked to some diseases. The four-phosphate adaptor protein FAPP2-mediated glucosylceramide (GlcCer) transport for complex GSL synthesis has been studied extensively. However, the molecular machinery of FAPP2 as a GlcCer-transferring protein remains poorly defined. Here, we identify a Golgi-resident protein, acyl-coenzyme A binding domain containing 3 (ACBD3), as an interacting partner of FAPP2. We find that ACBD3 knockdown leads to dramatic Golgi fragmentation, which subsequently causes FAPP2 dispersal throughout the cytoplasm and a decreased localization at trans-Golgi network. The further quantitative lipidomic analysis indicates that ACBD3 knockdown triggers abnormal sphingolipid metabolism. Interestingly, the expression of siRNA-resistant full-length ACBD3 can rescue these defects caused by ACBD3 knockdown. These data reveal critical roles for ACBD3 in maintaining the integrity of Golgi morphology and cellular sphingolipid homeostasis and establish the importance of the integrated Golgi complex for the transfer of GlcCer and complex GSL synthesis.